Improvement of Erection Related Incision Pain in Circumcision Patients using Interrupted Rapid Eye Movement Sleep: A Randomized Controlled Study - Dai, A-juan; Li, Miao; Wang, Li-li; Liu, Ting; Wang, Xiao-hua; Huang, Yu-hua (Urology Journal, 2018)
Introduction: Postoperative pain from male circumcision (MC) is common especially in the sleep-related erection period. This study aims to explore the effect of interrupted rapid eye movement (IREM) sleep on relieving SRE-related incision pain and the improvement of other clinical outcomes. Materials and Methods: This simple randomized controlled study was conducted between May and November 2016. Approval was obtained from the local ethical committee on 5 May 2016. Ninety participants who underwent male circumcision were divided into the interrupted rapid eye movement sleep group and the control group. The times and the cumulative time of erection-related moderate and severe pain in minutes at night for 3 days after the operation were observed and compared. We also compared the condition of the incision swelling and healing. Sleep time at night was used to evaluate the safety of interrupted rapid eye movement sleep. Results: For the first 3 days after the operation, the times of sleep-related erection pain were significantly decreased in the IREM sleep group (P = .010). Five patients reported that there was no pain during night. The cumulative time of erection-related moderate and severe pain was statistically decreased in the interrupted rapid eye movement sleep group (P = .034). After 3 days, there was no moderate and severe pain related to sleep-related erection in the 2 groups. There were no significant differences in incision swelling (P = .768), healing (P = .626), and sleep time (P = .231). Conclusion: Interrupted rapid eye movement sleep is an effective, simple, and free treatment to relieve incision pain of sleep-related erections.